What men want [videorecording (DVD)] - Henson, Taraji P; McLendon-Covey, Wendi, 1969-; Greenfield, Max, 1980-; Lutz, Kellan, 1985-; O'Neal, Shaquille; Roundtree, Richard, 1942- (Paramount Home Entertainment, 2019)
Ali Davis is left on the outside by her fellow sports agents because she is a woman in a male-dominated profession, but she acquires an unexpected edge when she develops the ability to hear men's thoughts.